Transcatheter closure of multiperforated atrial septal defect - Luis Cerdán Ferreira; Georgina Fuertes Ferre; Juan Sánchez-Rubio Lezcano; Marta López Ramón (REC: Interventional Cardiology (English Ed.))
ABSTRACT Introduction and objectives: Multi-fenestrated atrial septal defects (mASD) pose both diagnostic and therapeutic challenges. This study aimed to compare the outcomes of transcatheter closure in patients with mASD vs those with a single ASD at our center. Methods: We conducted a retrospective, single-center study including adult patients who underwent transcatheter ASD closure from October 2014 through October 2024. Demographic, echocardiographic, and hemodynamic data were collected, with a the 6-month follow-up. Results: A total of 67 patients were included, 12 of whom (18%) exhibited mASD. Patients with mASD were younger (42 vs 54 years) and more frequently presented with an interatrial septal aneurysm (91% vs 27%; P = .001). The use of multiple occlusion devices was more common in patients with mASD (34% vs 4%; P = .008). Complications were rare (5.9%) and none occurred in the mASD group. Procedural outcomes, including residual shunt and right ventricular remodeling at the follow-up, were comparable between groups. Conclusions: Transcatheter closure of mASD is both a safe and feasible procedure, with clinical outcomes similar to those observed in patients with a single ASD.